THE PLAYFUL PATH TO PROFICIENCY: THE IMPORTANCE OF USING GAMES IN TEACHING ENGLISH LANGUAGE - To’lqinova, Maftunaxon; Bekbergenova , Gulayim (Журнал иностранных языков и лингвистики, 2025)
The field of English Language Teaching (ELT) is constantly evolving, with educators seeking innovative and effective methodologies to cater to diverse learner needs and enhance language acquisition. Traditional methods, while providing a foundational understanding of grammar and vocabulary, can sometimes lack the dynamism needed to fully engage students and foster a genuine love for the language. In this context, the integration of games into the language classroom has emerged as a powerful pedagogical tool, offering a refreshing and enjoyable alternative to more conventional approaches. The inherent nature of games – their interactive, competitive, and often collaborative elements – aligns remarkably well with the principles of effective language learning. Games can create a low-pressure environment where students feel more comfortable taking risks, experimenting with language, and actively participating in communicative tasks. This article aims to delve into the multifaceted importance of utilizing games in ELT, exploring their cognitive, affective, and social benefits, and providing a framework for their practical application in diverse learning contexts.